THE FORMATION OF HISTOLOGY AS AN INDEPENDENT SCIENTIFIC DISCIPLINE ON MEDICAL FACULTY OF THE IMPERIAL MOSCOW UNIVERSITY IN THE MIDDLE OF XIX CENTURY (1860–1891) - S. L. Kuznetsov; C. S. Ghadzhieva (Сеченовский вестник, 2012)
The paper gives a brief outline of the institutional and cognitive structure of university education and science in Russia as an example of the morphological sciences at the medical faculty of the Imperial Moscow University. The contribution to the development of histology of the Imperial Moscow University professors — P.P. Einbrodt (Jr.), I.M.Sokolov, J.A. Borzenkova is analyzed. The authors examined the original documents on the history of the Physiological Institute (cabinet) at the Department of Physiology, healthy person (or rather — histological Cabinet department of histology, embryology and comparative anatomy) of the Medical Faculty of IMU.